Proses Toponimi Desa dan Dusun di Kecamatan Pulubala, Kabupaten Gorontalo, Provinsi Gorontalo: Penelitian - Zulkifli Wolionelo; Sayama Malabar; Herson Kadir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The objective of this research is to classify and describe the names of villages and hamlets based on three main aspects: physical manifestation, social structure, and cultural values. The theory used to analyze these issues is Sudaryat’s (2009) toponymy theory. This study employs an anthropolinguistic approach and adopts a qualitative descriptive research design. The research was conducted in the villages and hamlets located within Pulubala District, Gorontalo Regency, Gorontalo Province.The data in this study consist of the historical origins of the place names of villages and hamlets, obtained from both oral and written sources. Data collection was carried out through semi-structured interviews using elicitation techniques, face-to-face conversations, audio recordings, and note-taking. In addition, documentation techniques were also employed. The results of the study show that out of 11 villages and 37 hamlets examined, the toponymic processes reflect the community’s close relationship with geographical conditions (physical), social structure (founders, professions, migration), as well as cultural values and folklore (legends, myths). For instance, the name Titileya Hamlet refers to its geographical location between two rivers (physical aspect), while Pulubala Village derives its name from the history of a local royal organization (cultural aspect).